ANGPTL4 Regulates Psoriasis via Modulating Hyperproliferation and Inflammation of Keratinocytes - Zuo, Yuyue; Dai, Lei; Li, Li; Huang, Yuqiong; Liu, Xinxin; Liu, Xin; Duan, Xiaoru; Jiang, Su; Deng, Guo-Min; Chen, Hongxiang (Frontiers in Pharmacology, 2022)
Background: Psoriasis is characterized by keratinocyte proliferation and massive inflammatory leukocytes infiltration, affecting 0.14 1.99% of the world’s population. Our aim was to identify novel potential therapeutic strategies for psoriasis. Methods: Weighted gene co-expression network analysis (WGCNA) was performed to identify gene modules that were closely related to psoriasis based on the GSE30999 dataset, which contained expression data from 85 patients with moderate-to-severe psoriasis. Then, angiopoietin-like 4 (ANGPTL4), one of the most related hub genes, was selected for in vitro and in vivo functional assays. In our experiments, imiquimod (IMQ)-induced psoriasiform dermatitis in mice and human keratinocytes (HaCaT) cells were used to study the potential roles and mechanisms of ANGPTL4 in psoriasis. Results: WGCNA analysis revealed the turquoise module was most correlated with psoriasis, and ANGPTL4 is one of the most related hub genes that significantly upregulated in psoriasis lesions compared with non-lesional skin. Consistent with the bioinformatic analysis, the expression of ANGPTL4 was significantly upregulated in IMQ-induced psoriasiform skin of mice. Exogenous recombinant ANGPLT4 protein treatment could promote the proliferation and induce the expression of inflammatory cytokines in HaCaTs, whereas silencing of ANGPTL4 effectively inhibited these effects. Then we demonstrated that recombinant ANGPTL4 exacerbated psoriasiform inflammation and epidermal hyperproliferation in vivo. Mechanismly, extracellular signal-regulated kinase 1/2 (ERK1/2) and signal transducer and activator of transcription 3 (STAT3) pathways were involved in ANGPTL4-mediated regulation of proliferation and inflammation. Conclusion: We found ANGPTL4 was significantly increased in IMQ-induced psoriasiform skin of mice. ANGPTL4 could promote keratinocyte proliferation and inflammatory response via ERK1/2 and STAT3 dependent signaling pathways in psoriasis.